An innovative seismic-resilient bridge with shape memory alloy-washer-based footing rocking RC piers. (March 2021) - Zheng, Yue; Fang, Cheng; Liang, Dong; Sun, Ruiqin
This study proposes a new footing rocking pier which employs shape memory alloy (SMA) washers as its kernel elements. Apart from providing self-centering capability and energy dissipation, the SMA washers enable a "limited rocking" behavior for the pier, helping enhance the seismic resilience of the bridges. The study commences with quasi-static tests on SMA washer groups with various stack patterns. Subsequently, a 1/4 scale SMA-washer-based rocking pier specimen is tested. Following the experimental study, a bridge system adopting the SMA-washer-based rocking pier is carefully designed. An iterative seismic design approach is proposed for the rocking pier, followed by a system level analysis on the entire bridge system. A suite of ground motions corresponding to two intensity levels are considered. The performance of the innovative bridge is also compared with a conventional bridge with fixed-base piers. The results reveal that the new system exhibits superior performance to the conventional bridge in terms of pier damage control, which is achieved with acceptable sacrifice of other performance indices such as bearing displacement and peak drift ratio. A further parametric study suggests that the response of the bridge with the proposed pier is related to the load resistance and deformability of the SMA washers.